The vigorous imagination : New Scottish Art. - Scottish National Gallery of Modern Art, Edinburgh (Edinburgh : The Trustees of The National Galleries of Scotland, 1987)
Ainsley, Sam ; Braham, Philip ; Campbell, Steven ; Colvin, Calum ; Conroy, Stephen ; Currie, Ken ; Hardie, Gwen ; Howson, Peter ; Hughes, Ian ; Mach, David ; McIntyre, Keith ; O'Donnell, Ron ; Redfern, June ; Rossi, Mario ; Urie, Joseph ; Whiteford, Kate ; Wiszniewski, Adrian
The vigorous imagination : New Scottish Art, Scottish National Gallery of Modern Art, Edinburgh, 9 August - 25 October 1987
boek